2018
DOI: 10.1063/1.5025604
|View full text |Cite|
|
Sign up to set email alerts
|

Inter-layer and intra-layer heat transfer in bilayer/monolayer graphene van der Waals heterostructure: Is there a Kapitza resistance analogous?

Abstract: Van der Waals heterostructures have exhibited interesting physical properties. In this paper, heat transfer in hybrid coplanar bilayer/monolayer (BL-ML) graphene, as a model layered van der Waals heterostructure, was studied using non-equilibrium molecular dynamics (MD) simulations. Temperature profile and inter-and intra-layer heat fluxes of the BL-ML graphene indicated that, there is no fully developed thermal equilibrium between layers and the drop in average temperature profile at the step-like BL-ML inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The continuum model adapted from Ref. 31 to predicted the local temperature in our system using the heat equation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The continuum model adapted from Ref. 31 to predicted the local temperature in our system using the heat equation.…”
Section: Methodsmentioning
confidence: 99%
“…We intend to state here a continuum model according to Ref. 31 that can describe temperature distribution in a long PGG (i.e. >> 36Å).…”
Section: Continuum Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A theoretical study assigned thermal rectification properties to GJs [15], however this has not been examined experimentally. Other simulations also showed that heat transfer at GJs is non-trivial, because in the multilayer region different layers may have different temperatures [16]. Knowledge of heat flow across GJs is important not just fundamentally, but also for practical applications in terms of how they modify the overall thermal conductivity of graphene (as GBs do [10,17]), or where GJs could act as phonon filters).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrathin thickness of channels can facilitate fast heat dissipation and quick response to external stimuli. Moreover, 2D materials can be vertically stacked on arbitrary materials, enabling rich device operations and physics . The number of reports on 2D materials‐based synaptic devices has accordingly increased rapidly.…”
Section: Introductionmentioning
confidence: 99%